Optimasi Performa Kendaraan Listrik Konversi Honda Beat FI 110 CC Menggunakan Response Surface Method - Rizky Wiono Berlian; Sudirman Rizki Ariyanto (Jurnal Sains, Teknik, Ekonomi, dan Pendidikan, 2026)
The transportation sector's reliance on fossil fuels has driven the development of converted electric vehicles as a more economical alternative. However, the performance of these converted vehicles—specifically the torque of the Brushless DC (BLDC) motor—remains suboptimal due to a lack of systematic controller parameter settings. This study aims to analyze the effects of power limit and load on the electric motor torque of a converted Honda Beat FI 110 cc, develop a mathematical model using Response Surface Methodology (RSM), and determine the optimal parameter combination. A quantitative experimental approach was employed using a face-centered Central Composite Design (CCD), resulting in 13 experimental combinations. Independent variables included power limit (50%, 80%, and 100%) and load (60, 70, and 80 kg), while the dependent variable was torque, measured using a chassis dynamometer. Data were analyzed via second-order polynomial regression, ANOVA, a lack-of-fit test, and desirability optimization. The results showed torque values ​​ranging from 42.87 to 51.81 N·m, with the highest value achieved at a combination of 80% power limit and 70 kg load. The RSM model was statistically significant (F = 17.72; p = 0.001) and showed no lack of fit (p = 0.973). Optimization identified the best conditions at a power limit of 87.88% and a load of 70.10 kg, yielding a predicted torque of 49.66 N·m and a composite desirability value of 0.8197. This study demonstrates that the RSM-CCD approach is effective for modeling and optimizing the torque of converted electric vehicles, thereby serving as a reference for more systematic controller parameter settings.